Cation Selectivity in Biological Cation Channels Using Experimental Structural Information and Statistical Mechanical Simulation. - Justin John Finnerty; Alexander Peyser; Paolo Carloni (PLoS ONE)
Cation selective channels constitute the gate for ion currents through the cell membrane. Here we present an improved statistical mechanical model based on atomistic structural information, cation hydration state and without tuned parameters that reproduces the selectivity of biological Na+ and Ca2+ ion channels. The importance of the inclusion of step-wise cation hydration in these results confirms the essential role partial dehydration plays in the bacterial Na+ channels. The model, proven reliable against experimental data, could be straightforwardly used for designing Na+ and Ca2+ selective nanopores.